2019
DOI: 10.1177/0020294019858214
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative evaluation of the impurity content of grease for low-speed heavy-duty bearing using an acoustic emission technique

Abstract: Lubrication performance plays a key role in the lifetime of bearings. Online quantitative monitoring of the impurity contents of lubricants is an effective way to evaluate the performance of lubrication conditions. However, mainstream vibration monitoring techniques are often incapable of providing information on lubrication contamination especially for low-speed and high-load cases in which the dynamic interaction is insignificant. In this paper, an acoustic emission (AE) method is developed to achieve quanti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 26 publications
(18 reference statements)
0
8
0
Order By: Relevance
“…This microseismic data processing is mainly through MATLAB signal processing and visualization modules. The analysis method is based on the classic parameter analysis method of microseismic and acoustic emission signals [11], as shown in Fig. 5.…”
Section: Microseismic Data Analysis Methodsmentioning
confidence: 99%
“…This microseismic data processing is mainly through MATLAB signal processing and visualization modules. The analysis method is based on the classic parameter analysis method of microseismic and acoustic emission signals [11], as shown in Fig. 5.…”
Section: Microseismic Data Analysis Methodsmentioning
confidence: 99%
“…Therefore, it can be concluded that the collected fourth signal is the best one in this test process. To further validate the effectiveness, order spectrum analysis [37,38] is employed the collected signals. Figure 11 shows the corresponding envelope order spectrums those bearing signals.…”
Section: Data Processing and Verificationmentioning
confidence: 99%
“…The data statistics of correlation are given in Table 3. From the statistical resu it can reveal that the effective sensor placements are located in the first, second, fou To further validate the effectiveness, order spectrum analysis [37,38] is employed for the collected signals. Figure 11 shows the corresponding envelope order spectrums of those bearing signals.…”
Section: Data Processing and Verificationmentioning
confidence: 99%
“…The data types of data-driven method can be divided into single signal and multi-signal fusion. Single signal, such as vibration signal [3,18,[28][29][30], acoustic signal [31][32][33][34], current signal [24], [25], temperature signal [21], pressure signal [35], and instantaneous phase signal [36], etc., have been successfully applied to RC fault diagnosis. Although good diagnosis results have been achieved, the difficulty of data processing is increased because of the singleness of signal and the few effective fault features.…”
Section: Introductionmentioning
confidence: 99%